Peringkat Pemikiran Imam al-Ashʾari dalam Akidah - Wahab, Muhammad Rashidi (International journal of islamic thought, 2013)
Imam al-Ash’ari was the founder and leading figure of the Asha’irah sect of the Ahl al-Sunnah wa al-Jama’ah. His approach is often used as a main reference by Muslims since the time of its appearance until now concerning questions of faith. Some other schools of thought try to claim that the holding of Imam al-Ash’ari doctrine coincides with their beliefs. Imam al-Ash’ari is said to go through three stages of thought before he returned to the Ahl al-Sunnah wa al-Jama’ah at the end of his life to follow Imam Ahmad bin Hanbal the leadership of Salaf. Therefore, anyone who does not abide by the final stand of Imam al-Ash'ari, they are not considered as Asha’irah followers for conflicting Imam al-Ash’ari and Salaf scholars as recognized the best of generations. To assure the issues, this article is put forward to reexamine of the truth of the allegations either Imam al-Ash’ari has gone through three stages of thought or otherwise. Through document analysis method based on the works of Imam al-Ash’ari and his followers, the study found that Imam al-Ash’ari only used two stages of thought; Mu’tazilah initially and Ahl al-Sunnah wa al-Jama’ah in the end. Imam al-Ash’ari also used the tafwid Salaf and Khalaf interpretation methods especially in interacting with mutashabihat texts throughout his stay with the Ahl al-Sunnah wa al-Jama’ah. The study also identified that the disagreements among Asha’irah when determining the thoughts of Imam al-Ash’ari is due to their uncertainty about the exact date of his works written.